INDEKS STRUKTUR KOMUNITAS DAN SAPROBITAS PLANKTON SERTA CHECKLIST KEBERADAAN NEKTON DI PERAIRAN DANAU BERATAN, BALI - Gede Surya Indrawan; I Made Sara Wijana; I Made Saka Wijaya; Abd. Rahman As-syakur; I Putu Sugiana; I Made Yunarta (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2022)
Beratan Lake was mainly popular for tourism and aquaculture activities that affecting water's environmental characteristics. The water healthiness indicator can be seen through the organism's existence, namely plankton to nekton biota that can be uses as an essential parameter in monitoring water conditions. This study aims to determine the plankton community structure index, saprobity index and the presence of nektons in the Beratan Lake. Plankton were sampled using the pouring method while the nekton sample was taken randomly through direct sampling with fishing nets and conducted interviews with the surrounding local community and fishermen. The results of the study found that the abundance of phytoplankton was dominated by Staurastrum with abundance level 1,836.92 ind/L. Meanwhile, the zooplankton was dominated by Rotifera with abundance level 8.17 ind/L. The diversity index, uniformity and dominance of phytoplankton are 1.31, 0.60 and 0.33 respectively, while the saprobity index is 1.08 which classifies the waters of Beratan Lake as being in a lightly polluted condition. There were 18 species of nektons in Beratan Lake were found, with one endemic species Rasbora balinensis and 13 foreign fish. There also an invasive species, namely zebrafish (Amatitlania nigrofasciata) was found in this Lake. From the results of the study, we hope that the government in cooperation with the surrounding community, can control the ecological conditions of the waters of Beratan Lake, especially the presence of invasive species which are increasing in number, as well as protect endemic species. Keywords: Abundance; beratan lake; community structure; plankton; saprobity